If it's not what You are looking for type in the equation solver your own equation and let us solve it.
((4/7)*x^14)/3 = 0
35 = (4/6)*x-34
x^5-2*x^4+2*x^2-x-6;x-2
abs((1-x)/(x+1)) = 0
(2*z)/7-6 = 7
| 24x^3-56x^2+15x-35=0 | | 2(k-4)=(2k-8) | | 3u-11=46 | | 3(2x-18)=31+x | | 4/7x14/3 | | cos(3x)*3cos(3x)= | | 64-t^3= | | 5f+17=7f+5 | | 7a-4=(3a+9)+4a | | 900c^2=3600 | | 35=4/6x-34 | | 5y+9=54 | | -5x-1=7x+23 | | 9x^3+15x^2+25x+11=0 | | 2z/7-6=7 | | 14y^2-41y+27=0 | | 13a+12=80-13 | | 0-6y=24 | | 6x^5+8x^2=0 | | 25.12=1/2(12.56h) | | -10=18x | | -x/2a=9 | | 2*(3+4x)+2*x=86 | | -.8a-8=-.2a | | -b/2a=9 | | 7/9x=50 | | x-1/3=48 | | 6n+9=9n+(-3n)+9 | | 4(o+4)=-12 | | -6xy+2y^2-4y=0 | | x+6+2x=25 | | X^3y^2+x^2y-72x=0 |